Artesunate-amodiaquine versus artesunatesulfadoxine- pyrimethamine for uncomplicated falciparum malaria in children - Novie H. Rampengan; Jane Metusala; Ronald Chandra; Praevilia Salendu (Indonesian Pediatric Society, 2014)
Background Malaria is a major cause of morbidity and mortalityin children, especially in developing countries. Art emisinincombination therapy (ACT) has higher rates of parasite clearanceand inhibition of anti-malarial drugs resistance than non-ACT.Hence, we compared the efficacies of artesunate-amodiaquine(AS-AQ) versus artesunate-sulfadoxine pyrimethamine (AS-SP)combination therapies in children with uncomplicated falciparummalaria.Objective To compare the fever clearance time, parasite clearancetime, and length of hospital stay in uncomplicated falciparummalaria patients treated with AS-AQ and AS-SP.Methods We reviewed the medical records of children aged 1- 14years with uncomplicated falciparum malaria admitted to Prof.Dr. R. D. Kandou Hospital between January 2002 - June 2010.Treatment efficacy was evaluated by fever clearance time, parasiteclearan ce time, and length of hospital stay. The differencesof treatment efficacy between the two groups of therapy werean alyzed by independent T test.Results We identified 185 children with uncomplicatedfalciparum malaria, 104 cases were treated with AS-AQ whilethe other 81 received AS-SP. Parasite clearance time was shorterin AS-AQ group than in AS-SP group at 1.38 (SD 0.69) versus1.91 (SD 0.93) days, respectively (95%CI of differences 0.3 0 to0. 76, P<0.05) . The length of hospital stay was shorterin AS-AQgroup than in the AS-SP group, at 5.01 (SD 1.22) versus 6.04(SD 0.98) days, respectively (95%CI of differences 0. 71 to 1.35,P < 0.05). However, there was no statistically significant differencein fever clearance time between the groups.Conclusion AS-AQ combination therapy reduces parasiteclearance time and length of hospital stay compared to AS-SP46 • Paediatrlndones, Vol. 54, No. 1, January 2014combination therapy in children with uncomplicated falciparummalaria.